Acidentes com material biológico na Odontologia: uma revisão de literatura - MELO, Adrielle Alves de (2023)
In dentistry, biosafety aims to prevent or eliminate possible risks inherent to dental practice. However, the inadequate exercise of biosafety rules, contributes to the occurrence of accidents that involve biological material many times loaded of pathogenic microorganisms. Thus, this literature review sought to characterize the accidents, investigating the following factors: the public, the sex involved, the instrumental cause, the type of accident, the part of the body affected, the time of the accident and the measures after exposure. A bibliographic search of scientific articles was performed in the SCIELO, BBO and LILACS databases where 63 articles were identified where 26 were discarded and 27 selected. Of the latter, 14 were used as samples for analysis and discussion. From the analysis, it was identified that students are more involved in accidents, these occur more frequently among females, the main instrumental cause is the needle, the most common type of accident is the puncture, the most affected part of the body is the hands, accidents happen mainly during patient care and post exposure measures are performed, but need to be investigated in other studies. It is essential to emphasize biosafety education from the time of graduation and obtain greater control by the competent authorities and universities regarding the occurrence of accidents and the necessary and mandatory protocols after exposure.